Facial apocrine chromhidrosis. - Bonifazi, E.; Garofalo, L. (European Journal of Pediatric Dermatology, 2004)
Apocrine chromhidrosis is a rare condition -more frequent in the hyperpigmented races- characterized by secretion after emotional or pressure stimuli of green, blue or black apocrine sweat (4), caused by a lipofuscin pigment. Chromhidrosis usually starts in the peripuberal period (4) affecting areas with apocrine glands. However, it can affect also other areas such as the face (1, 3, 5), due to the presence of ectopic apocrine glands that can be histologically shown. It should be differentiated from pigmentation secondary to contact with metals or colored clothes (2) and, thanks to bacteriological examination, from pseudochromhidrosis induced by bacterial products. The most effective treatment is capsaicin, blocking substance P (3).